Preparation method of MOF-based ultrathin pressure-sensitive film

By using the MOF-based ultra-thin pressure-sensitive film preparation method with sandwich structure, nano-sized MOF materials are prepared by ultrasonic crushing and scraping method, combined with polymer materials, the problems of poor uniformity and stability of existing MOF films are solved, and high-resolution interface pressure detection is achieved.

CN119823433APending Publication Date: 2025-04-15SUN YAT SEN UNIV

Patent Information

Application Number
CN202411806607.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing MOF films have poor uniformity and poor stability, making it difficult to achieve high-resolution interface pressure detection.

Method used

The preparation method of MOF-based ultra-thin pressure-sensitive film with a sandwich structure is the top layer and the bottom layer is the encapsulation layer, and the middle layer is the nano-sized MOF material synthesized by ultrasonic crushing method. The MOF layer is prepared by scraping coating method, and polymer material is combined to improve the uniformity and stability of the film.

Benefits of technology

Continuous and uniform preparation of MOF films is achieved, with a thickness as low as 5μm, improving the stability of the film and high-resolution interface pressure detection capability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823433A_ABST
    Figure CN119823433A_ABST
Patent Text Reader

Abstract

The invention relates to the field of piezochromic films, in particular to a preparation method of an MOF-based ultrathin pressure-sensitive film which is of a sandwich structure, the top layer and the bottom layer are packaging layers, and the middle layer is an MOF layer. According to the method, the thickness of the MOF material is greatly reduced on the premise that the structure and the piezochromic performance of the MOF material are not damaged, and the continuous and uniform MOF-based ultrathin pressure-sensitive film is prepared; the MOF layer provided by the invention is prepared from an MOF material and a polymer, the uniformity and the stability of the MOF-based ultrathin pressure-sensitive film are improved by mixing the polymer material and the MOF material in the preparation process of the MOF-based ultrathin pressure-sensitive film, the invention provides a sandwich MOF film structure, the middle MOF layer is packaged by adopting upper and lower layers of macromolecules, and the MOF-based ultrathin pressure-sensitive film has the advantages that the MOF-based ultrathin pressure-sensitive film is prepared by adopting the MOF layer. The packaging layer is low in gas transmission rate and can effectively isolate water vapor, so that the stability of the MOF-based ultrathin pressure-sensitive film in the using process can be effectively improved, and the MOF-based ultrathin pressure-sensitive film has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of piezochromic films, and in particular to a method for preparing an MOF-based ultra-thin pressure-sensitive film. Background Art

[0002] In many fields such as precision parts assembly, chip packaging, nanoimprinting, and soft-pack battery packaging, accurate interface pressure detection is a key technology to improve product yield. Existing interface pressure detection methods can be divided into two categories: optical and electrical methods. Among them, the electrical method is to achieve quantitative measurement of interface pressure by detecting the electrical signal (such as resistance, voltage, capacitance, etc.) of the pressure sensor array. Due to the poor stability of the electrical signal during the pressure detection process and the limited size of a single array sensor unit, this type of sensor cannot achieve high stability and high resolution interface pressure detection; the optical method is a thin film sensor made of pressure-sensitive materials that change color under pressure, and the color change of the film before and after pressure is detected to achieve visual detection of interface pressure. This type of optical pressure sensor does not require complex circuits and micro-nano processing processes. The visual detection results of the interface pressure can be obtained by analyzing the pictures before and after pressure.

[0003] Pressure sensing films based on optical detection methods can be divided into four categories according to the sensing principle: microcapsule structure, photonic crystal, molecular structure transformation, and crystal structure transformation. Among them, microcapsule structure is often used in commercial pressure-sensitive films. Under the action of pressure, the microcapsule ruptures, causing the internal colorant to seep out and contact with the developer to detect color changes. Due to the large size of the microcapsules and the large permeation area after rupture, accurate high-resolution pressure measurement cannot be achieved; the periodic structure in the photonic crystal changes color under pressure, but the color cannot be maintained after the pressure is released, so it is not suitable for interface stress detection; the synthesis process of pressure-sensitive materials based on molecular structure transformation is complex, the pressure sensing range is narrow, and structural transformation can only occur under greater pressure; and pressure-sensitive materials based on crystal structure transformation, such as MOF, are ideal materials for interface pressure detection films. However, due to the large particle size and uneven particle size distribution of MOF materials, it is still very challenging to prepare MOF into a uniform pressure-sensitive film that can detect interface stress.

[0004] For example, the patent document CN113198331B discloses a method for preparing a small-sized amorphous MOF mixed matrix membrane with high selectivity, and the preparation process includes: firstly, using polymer-polyethyleneimine to induce the synthesis of a small-sized MOF material UiO-66-NH2, then heat-treating the material to convert it into an amorphous state, and evenly mixing AS-UiO-66-NH2 with polymer PVAm as a casting liquid, and coating the casting liquid on a polysulfone substrate modified with PDMS and PVA and having a uniform hydrophilic interface layer, and forming a PVAm / AS-Ui0-66-NH2 / MPSf gas separation membrane with high selectivity through interface self-assembly. This invention improves the film-forming property, but the formed membrane has poor uniformity, high roughness, and poor stability.

[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a method for preparing a MOF-based ultra-thin pressure-sensitive film. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a method for preparing a MOF-based ultra-thin pressure-sensitive film to solve the problems of poor uniformity and poor stability of MOF films in the prior art.

[0007] Based on the above purpose, the present invention provides a method for preparing a MOF-based ultra-thin pressure-sensitive film.

[0008] A method for preparing a MOF-based ultra-thin pressure-sensitive film, characterized in that the MOF-based ultra-thin pressure-sensitive film is a sandwich structure, the top layer and the bottom layer are encapsulation layers, and the middle layer is a MOF layer;

[0009] The encapsulation layer is made of encapsulation material, and the thickness of the encapsulation layer is 1-2 μm;

[0010] The MOF layer is synthesized by ultrasonic crushing method to form a nano-sized MOF material with piezochromic properties, and the MOF layer is prepared by scraping method, and the thickness of the MOF layer is 4-5 μm;

[0011] The MOF-based ultra-thin pressure-sensitive film can realize visual pressure detection.

[0012] Preferably, the packaging material includes any one of the following:

[0013] Epoxy resins, polyimides, polyurethanes, polyvinyl alcohol, polyethylene terephthalate, polydimethylsiloxane, polycarbonate and paraxylene polymers.

[0014] Preferably, the method for preparing a MOF-based ultra-thin pressure-sensitive film according to claim 1 is characterized in that the nano-sized MOF synthesis method is an ultrasonic crushing method, the dosage ratio of MOF material to N,N-dimethylformamide is 28-32 mg: 3-5 mL, the ultrasonic crushing power is 19.5-20.5 KHz, and the ultrasonic time is 1-2 h.

[0015] Preferably, the piezochromic MOF material comprises at least one of the following materials:

[0016] LIFM-66, PCN-128, NKU-200-Eu, HNU-49, DEF® ZnETTB and LIFM-102.

[0017] Preferably, during the preparation of the MOF layer, the MOF is dispersed in a polymer solution, and the polymer includes any one of the following:

[0018] Polyethylene, polypropylene, polyvinyl chloride, polystyrene, polycarbonate, polymethyl methacrylate, polyamide, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyvinyl pyrrolidone, polydimethylsiloxane, polylactic acid, polycaprolactone, polybutylene succinate.

[0019] Preferably, the MOF layer preparation process is a doctor blade coating method, and the specific steps are as follows:

[0020] Step A1: dispersing the nano-sized piezochromic MOF material in a polymer solution to prepare a scraping dispersion solution, and taking 50-60 μL of the scraping dispersion solution;

[0021] Step A2: Set the scraper height to 10-30 μm and the speed to 55-62 mm·min -1 ;

[0022] Step A3: Place the scraped MOF layer on a 95-105°C heating plate for 1-3 min.

[0023] Preferably, the calculation method for quantifying the pressure distribution in the compressed area is: first, collecting images of the pressure-sensitive film before and after the compression, and using an image processing algorithm to extract the characteristic values ​​of the images before and after the compression, and then calculating the color difference ΔE, and establishing a linear relationship between ΔE and the pressure magnitude, and finally realizing visual detection of the pressure distribution by performing color difference calculation on the collected images.

[0024] Preferably, the MOF-based ultra-thin pressure-sensitive film is used in the fields of piezochromic film preparation and interface stress detection.

[0025] Beneficial effects of the present invention:

[0026] The present invention greatly reduces the thickness of the MOF material without destroying the structure and piezochromic performance of the MOF material, and prepares a continuous and uniform MOF-based ultra-thin pressure-sensitive film, and the thickness of the pressure-sensitive film is as low as 5μm; the MOF layer provided by the present invention is prepared from MOF material and polymer, and in the preparation process of the MOF-based ultra-thin pressure-sensitive film, the polymer material is mixed with the MOF material to improve the uniformity and stability of the MOF-based ultra-thin pressure-sensitive film.

[0027] The present invention provides a sandwich MOF film structure, which uses an upper and lower layer of polymer to encapsulate the MOF in the middle. Since the gas permeability of the encapsulation layer is low, it can effectively isolate water vapor. Therefore, the sandwich encapsulation structure can effectively improve the stability of the MOF-based ultra-thin pressure-sensitive film during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 Schematic diagram of the structure of the MOF-based ultra-thin pressure-sensitive film prepared in Example 1 of the present invention, the top layer and the bottom layer are encapsulation layers, and the middle layer is a MOF layer;

[0030] Figure 2 This is a schematic diagram of the structure of the resolution test mold in the present invention;

[0031] Figure 3 This is a diagram of the pressure test results in the present invention. DETAILED DESCRIPTION

[0032] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0033] The sources and properties of some of the raw materials used in the present invention are as follows:

[0034] LIFM-66 is derived from "Visualization of Anisotropic and Stepwise Piezofluorochromism in an MOF Single Crystal" published by Mei Pan et al. in Chem; PCN-128 is derived from "Piezofluorochromic Metal-Organic Framework: A MicroScissor Lift" published by Jie Su et al. in Journal of the American Chemical Society; NKU-200-Eu is derived from "Real-Time In Situ Volatile Organic Compound Sensing by a Dual-Emissive Polynuclear Ln-MOF with Pronounced LnIII Luminescence Response" published by Zhao-Quan Yao et al. in Angewandte Chemie International Edition; HNU-49 is derived from "Dual-emitting piezofluorochromic dye@MOF for white-light generation" published by Weiting Yang et al. in Chemical Communications; LIFM-102 is derived from "One and Two-Photon Excited Fluorescence Optimization of Metal–Organic Frameworks with Symmetry-Reduced AIEgen-Ligand”; DEF∈ZnETTB comes from “Smart Tetraphenylethene-Based Luminescent Metal–Organic Frameworks with Amide-Assisted Thermofluorochromics and Piezofluorochromics” published by Ben Zhong Tang et al. in Advanced Science.

[0035] Embodiment 1: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0036] S1: 28 mg of LIFM-66 was dispersed in 3 mL of N, N-dimethylformamide, and filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation. The power of the ultrasonic crusher was 19.5 KHz, the ultrasonication time was 1 h, the speed of the centrifuge was 8000 rpm, and the centrifugation time was 2 min.

[0037] S2: 12 mg MOF precipitate, 4 mg polyethylene and 40 mg water were mixed to obtain a blade coating dispersion;

[0038] S3: Use epoxy resin to deposit the bottom encapsulation layer on a clean glass sheet, take 50 μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 95°C heating plate and heat it for 1 min, then use epoxy resin to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 10 μm and the coating speed is 55 mm min -1 The thickness of the prepared encapsulation layer is 1 μm, and the thickness of the MOF layer is 4 μm.

[0039] Embodiment 2: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0040] S1: 29 mg PCN-128 was dispersed in 4 mL N, N-dimethylformamide, and filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation, wherein the power of the ultrasonic crusher was 20 KHz, the ultrasonication time was 1 h, the speed of the centrifuge was 8200 rpm, and the centrifugation time was 3 min;

[0041] S2: 13 mg of MOF precipitate, 4.1 mg of polypropylene and 41 mg of water were mixed to obtain a blade coating dispersion;

[0042] S3: Use polyimide to deposit the bottom encapsulation layer on a clean glass sheet, take 52μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 98℃ heating plate and heat it for 1 minute, then use polyimide to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 12μm and the coating speed is 56mm·min -1 The thickness of the prepared encapsulation layer is 1 μm, and the thickness of the MOF layer is 4 μm.

[0043] Embodiment 3: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0044] S1: 30 mg NKU-200-Eu was dispersed in 4 mL N, N-dimethylformamide, and filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation. The power of the ultrasonic crusher was 20 KHz, the ultrasonication time was 1.5 h, the speed of the centrifuge was 8600 rpm, and the centrifugation time was 4 min.

[0045] S2: 14 mg MOF precipitate, 4.2 mg polyvinyl chloride and 42 mg water were mixed to obtain a blade coating dispersion;

[0046] S3: Use polyvinyl alcohol to deposit the bottom encapsulation layer on a clean glass sheet, take 56 μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 100°C heating plate and heat it for 3 minutes, then use polyvinyl alcohol to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 15 μm and the coating speed is 59 mm min -1 The thickness of the prepared encapsulation layer is 1 μm, and the thickness of the MOF layer is 4 μm.

[0047] Embodiment 4: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0048] S1: 31 g HNU-49 was dispersed in 5 mL N, N-dimethylformamide, and filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation, wherein the power of the ultrasonic crusher was 20 kHz, the ultrasonication time was 2 h, the speed of the centrifuge was 8800 rpm, and the centrifugation time was 5 min;

[0049] S2: 17 mg MOF precipitate, 4.3 mg polystyrene and 43 mg water were mixed to obtain a blade coating dispersion;

[0050] S3: Use polyethylene terephthalate to deposit the bottom encapsulation layer on a clean glass sheet, take 58 μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 102°C heating plate and heat it for 3 minutes, then use polyethylene terephthalate to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 28 μm and the coating speed is 60 mm min -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0051] Embodiment 5: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0052] S1: 31 g of LIFM-102 was dispersed in 5 mL of N, N-dimethylformamide, and the mixture was filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation. The power of the ultrasonic crusher was 20 kHz, the ultrasonication time was 2 h, the speed of the centrifuge was 8800 rpm, and the centrifugation time was 5 min.

[0053] S2: 17 mg MOF precipitate, 4.3 mg polycarbonate and 43 mg water were mixed to obtain a blade coating dispersion;

[0054] S3: Use polydimethylsiloxane to deposit the bottom encapsulation layer on a clean glass sheet, take 58μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 102℃ heating plate and heat it for 3 minutes, then use polydimethylsiloxane to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 28μm and the coating speed is 60mm·min -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0055] Embodiment 6: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0056] S1: 31 g LIFM-66 was dispersed in 5 mL N, N-dimethylformamide, and filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation, wherein the power of the ultrasonic crusher was 20 kHz, the ultrasonication time was 2 h, the speed of the centrifuge was 8800 rpm, and the centrifugation time was 5 min;

[0057] S2: 17 mg of MOF precipitate, 4.3 mg of polymethyl methacrylate and 43 mg of water were mixed to obtain a blade coating dispersion;

[0058] S3: On a clean glass sheet, a p-xylene polymer was used to deposit a bottom encapsulation layer. 58 μL of the coating dispersion was taken and the scraper height was adjusted to scrape the bottom encapsulation layer to form an intermediate MOF layer. The layer was placed on a 102°C heating plate and heated for 3 min. Then, a p-xylene polymer was used to deposit an encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film. The scraper height was 28 μm and the coating speed was 60 mm min. -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0059] Embodiment 7: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0060] S1: 31 g DEF∈ZnETTB was dispersed in 5 mL N, N-dimethylformamide, and filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation, wherein the power of the ultrasonic crusher was 20 kHz, the ultrasonication time was 2 h, the speed of the centrifuge was 8800 rpm, and the centrifugation time was 5 min;

[0061] S2: 17 mg MOF precipitate, 4.3 mg polyamide and 43 mg water were mixed to obtain a blade coating dispersion;

[0062] S3: Polycarbonate was used to deposit the bottom encapsulation layer on a clean glass sheet, 58 μL of the coating dispersion was taken and the scraper height was adjusted to scrape the bottom encapsulation layer to form an intermediate MOF layer, which was placed on a 102°C heating plate and heated for 3 min, and then polycarbonate was used to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height was 28 μm and the coating speed was 60 mm min -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0063] Embodiment 8: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0064] S1: 32 mg of LIFM-66 was dispersed in 5 mL of N, N-dimethylformamide, and the mixture was filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation. The power of the ultrasonic crusher was 20.5 KHz, the ultrasonication time was 2 h, the speed of the centrifuge was 9000 rpm, and the centrifugation time was 5 min.

[0065] S2: 18 mg of MOF precipitate, 4.5 mg of polyethylene terephthalate and 45 mg of water were mixed to obtain a blade coating dispersion;

[0066] S3: Use polycarbonate to deposit the bottom encapsulation layer on a clean glass sheet, take 60 μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 105°C heating plate and heat it for 3 minutes, then use polycarbonate to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 30 μm and the coating speed is 62 mm min -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0067] Embodiment 9: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0068] S1: 32 mg of LIFM-66 was dispersed in 5 mL of N, N-dimethylformamide, and the mixture was filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation. The power of the ultrasonic crusher was 20.5 KHz, the ultrasonication time was 2 h, the speed of the centrifuge was 9000 rpm, and the centrifugation time was 5 min.

[0069] S2: 18 mg of MOF precipitate, 4.5 mg of acrylonitrile-butadiene-styrene copolymer and 45 mg of water were mixed to obtain a blade coating dispersion;

[0070] S3: Use polycarbonate to deposit the bottom encapsulation layer on a clean glass sheet, take 60 μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 105°C heating plate and heat it for 3 minutes, then use polycarbonate to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 30 μm and the coating speed is 62 mm min -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0071] Embodiment 10: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0072] S1: 32 mg of LIFM-66 was dispersed in 5 mL of N, N-dimethylformamide, and the mixture was filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation. The power of the ultrasonic crusher was 20.5 KHz, the ultrasonication time was 2 h, the speed of the centrifuge was 9000 rpm, and the centrifugation time was 5 min.

[0073] S2: 18 mg MOF precipitate, 4.5 mg polyvinyl pyrrolidone and 45 mg water were mixed to obtain a blade coating dispersion;

[0074] S3: Use polycarbonate to deposit the bottom encapsulation layer on a clean glass sheet, take 60 μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 105°C heating plate and heat it for 3 minutes, then use polycarbonate to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 30 μm and the coating speed is 62 mm min -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0075] Embodiment 11: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0076] S1: 32 mg of LIFM-66 was dispersed in 5 mL of N, N-dimethylformamide, and the mixture was filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation. The power of the ultrasonic crusher was 20.5 KHz, the ultrasonication time was 2 h, the speed of the centrifuge was 9000 rpm, and the centrifugation time was 5 min.

[0077] S2: 18 mg of MOF precipitate, 4.5 mg of polydimethylsiloxane and 45 mg of water were mixed to obtain a blade coating dispersion;

[0078] S3: Use polycarbonate to deposit the bottom encapsulation layer on a clean glass sheet, take 60 μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 105°C heating plate and heat it for 3 minutes, then use polycarbonate to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 30 μm and the coating speed is 62 mm min -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0079] Embodiment 12: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0080] S1: 32 mg of LIFM-66 was dispersed in 5 mL of N, N-dimethylformamide, and the mixture was filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation. The power of the ultrasonic crusher was 20.5 KHz, the ultrasonication time was 2 h, the speed of the centrifuge was 9000 rpm, and the centrifugation time was 5 min.

[0081] S2: 18 mg MOF precipitate, 4.5 mg polylactic acid and 45 mg water were mixed to obtain a blade coating dispersion;

[0082] S3: Use polycarbonate to deposit the bottom encapsulation layer on a clean glass sheet, take 60 μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 105°C heating plate and heat it for 3 minutes, then use polycarbonate to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 30 μm and the coating speed is 62 mm min -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0083] Embodiment 13: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0084] S1: 32 mg of LIFM-66 was dispersed in 5 mL of N, N-dimethylformamide, and the mixture was filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation. The power of the ultrasonic crusher was 20.5 KHz, the ultrasonication time was 2 h, the speed of the centrifuge was 9000 rpm, and the centrifugation time was 5 min.

[0085] S2: 18 mg of MOF precipitate, 4.5 mg of polycaprolactone and 45 mg of water were mixed to obtain a blade coating dispersion;

[0086] S3: Use polycarbonate to deposit the bottom encapsulation layer on a clean glass sheet, take 60 μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 105°C heating plate and heat it for 3 minutes, then use polycarbonate to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 30 μm and the coating speed is 62 mm min -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0087] Example 14: A method for preparing a MOF-based ultra-thin pressure-sensitive film, comprising the following steps:

[0088] S1: 32 mg of LIFM-66 was dispersed in 5 mL of N, N-dimethylformamide, and the mixture was filtered after ultrasonication using an ultrasonic crusher. The filtrate was collected and centrifuged to obtain MOF precipitation. The power of the ultrasonic crusher was 20.5 KHz, the ultrasonication time was 2 h, the speed of the centrifuge was 9000 rpm, and the centrifugation time was 5 min.

[0089] S2: 18 mg of MOF precipitate, 4.5 mg of polybutylene succinate and 45 mg of water were mixed to obtain a blade coating dispersion;

[0090] S3: Use polycarbonate to deposit the bottom encapsulation layer on a clean glass sheet, take 60 μL of the coating dispersion and adjust the scraper height to scrape the bottom encapsulation layer to form an intermediate MOF layer, place it on a 105°C heating plate and heat it for 3 minutes, then use polycarbonate to deposit the encapsulation layer on the top to obtain a MOF-based ultra-thin pressure-sensitive film, where the scraper height is 30 μm and the coating speed is 62 mm min -1 The thickness of the prepared encapsulation layer is 2 μm, and the thickness of the MOF layer is 5 μm.

[0091] Comparative Example 1:

[0092] Compared with Example 1, this comparative example does not add an encapsulation layer during the preparation process of the MOF-based ultra-thin pressure-sensitive film, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a MOF-based ultra-thin pressure-sensitive film is obtained.

[0093] Comparative Example 2:

[0094] Compared with Example 1, this comparative example only increases the thickness of the encapsulation layer from "1 μm" to "50 μm", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a MOF-based ultra-thin pressure-sensitive film is obtained.

[0095] Comparative Example 3:

[0096] Compared with Example 1, this comparative example only increases the thickness of the MOF layer from "4 μm" to "50 μm", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a MOF-based ultra-thin pressure-sensitive film is obtained.

[0097] Comparative Example 4:

[0098] Compared with Example 1, this comparative example only replaces "polyethylene" with "natural rubber", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a MOF-based ultra-thin pressure-sensitive film is obtained.

[0099] Performance Test:

[0100] Resolution performance test:

[0101] A copper layer with a thickness of 100nm is deposited on a clean glass sheet, and then a layer of photoresist is spin-coated on the copper layer. Stripe patterns of different widths are prepared on the photoresist using a maskless photolithography method. After development, stripe patterns of different widths are etched on the copper layer using a wet etching method to obtain a copper mask. Next, a high-hardness UV glue is scraped on the top of the copper mask, and the UV glue on the top is cured through the copper mask. The uncured part is washed away to obtain a resolution test press with different widths, such as Figure 2 as shown in .

[0102] The MOF-based ultra-thin pressure-sensitive film prepared in Example 1 is placed on a resolution test press, and pictures of the MOF-based ultra-thin pressure-sensitive film before and after being compressed are collected under different pressures, and the characteristic values ​​(l0, a0, b0) and (l, a, b) of the pictures before and after being compressed are extracted. The color difference ΔE under different pressures is calculated, and ΔE is linearly fitted with the pressure to obtain a fitting function. In the process of quantitative analysis of interface stress, ΔE of each pixel point of the collected picture is calculated, and the numerical value of the pressure is inferred through the fitting function, so as to achieve quantitative measurement of the interface stress, such as Figure 3 As shown, it can be seen that the MOF-based ultra-thin pressure-sensitive film prepared in Example 1 collapses under the action of pressure, causing the crystal color to change, and ultra-high resolution interface stress visualization detection can be achieved in interface stress detection.

[0103] The calculation formula for color difference ΔE is:

[0104] Uniformity test:

[0105] Fifteen points were randomly selected from the MOF-based ultra-thin pressure-sensitive films prepared in Examples 1 to 14 and Comparative Examples 1 to 4, and the thickness of the 15 points on the MOF film was measured using an interferometer to calculate the standard deviation of the thickness.

[0106] Stability test:

[0107] The MOF-based ultra-thin pressure-sensitive films prepared in Examples 1 to 14 and Comparative Examples 1 to 4 were subjected to stability tests using a thermogravimetric analyzer. The obtained data were processed to obtain differential thermogravimetric analysis data, and the thermal decomposition temperature of the MOF-based ultra-thin pressure-sensitive films was obtained.

[0108] The performance was tested under a three-electrode system. The MOF-based ultra-thin pressure-sensitive films prepared in Examples 1 to 14 and Comparative Examples 1 to 4 were used as working electrodes, platinum wires as counter electrodes, and Ag / AgC1 as reference electrodes. The three-electrode system was placed in an electrolyte, and a voltage of -1 to 1V was applied for a period of 20s. The transmittance at 600nm was tested in an ultraviolet-visible spectrophotometer at a wavelength of 600nm. The light modulation retention rate was tested after 1500 cycles.

[0109] Table 1 Summary of test results of Examples 1-5 and Comparative Examples 1-5

[0110]

[0111]

[0112] Data Analysis:

[0113] The MOF-based ultra-thin pressure-sensitive film prepared by the present invention has high resolution, high stability and high uniformity; the present invention greatly reduces the thickness of the MOF material without destroying the structure and piezochromic performance of the MOF material, and prepares a continuous and uniform MOF-based ultra-thin pressure-sensitive film, and the thickness of the pressure-sensitive film is as low as 5μm; the MOF layer provided by the present invention is prepared from MOF material and polymer, and in the process of preparing the MOF-based ultra-thin pressure-sensitive film, the polymer material is mixed with the MOF material to improve the uniformity and stability of the MOF-based ultra-thin pressure-sensitive film.

[0114] The present invention provides a sandwich MOF film structure, which uses an upper and lower layer of polymer to encapsulate the MOF in the middle. Since the gas permeability of the encapsulation layer is low, it can effectively isolate water vapor. Therefore, the sandwich encapsulation structure can effectively improve the stability of the MOF-based ultra-thin pressure-sensitive film during use.

[0115] It can be seen from Table 1 that the MOF-based ultra-thin pressure-sensitive film prepared by the present invention has higher uniformity and stability; while in Comparative Example 1, since the encapsulation layer is not added during the preparation process of the MOF-based ultra-thin pressure-sensitive film, it can be seen from Table 1 that the stability of the MOF-based ultra-thin pressure-sensitive film decreases, and the light modulation retention rate also decreases. This may be because the absence of the encapsulation layer cannot effectively isolate water vapor, and the stability of the prepared MOF-based ultra-thin pressure-sensitive film will decrease; Comparative Example 2 only increases the thickness of the encapsulation layer from "1μm" to "50μm". It can be seen from Table 1 that the uniformity of the MOF-based ultra-thin pressure-sensitive film decreases, and the light modulation retention rate also decreases. This may be because the encapsulation layer is too thick and the MOF layer content is relatively small, which may lead to the retention rate after multiple cycles in the battery. Decreased; Comparative Example 3 only increases the thickness of the MOF layer from "4μm" to "50μm". It can be seen from Table 1 that the uniformity of the MOF-based ultra-thin pressure-sensitive film decreases, and the light modulation retention rate also decreases. This may be because the MOF base is too thick, the sensitivity to pressure decreases, the roughness of the MOF film increases, and the uniformity decreases; Comparative Example 4 only replaces "polyethylene" with "natural rubber". It can be seen from Table 1 that the stability of the MOF-based ultra-thin pressure-sensitive film decreases, and the light modulation retention rate decreases after 1500 cycles. This may be because the ligand in the preparation of MOF material is replaced by natural rubber from polyethylene, and the MOF ligand cannot be well coordinated with the metal to form a metal organic skeleton, and polyethylene can be well combined with the metal, making the MOF-based ultra-thin pressure-sensitive film have better performance.

[0116] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0117] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a MOF-based ultra-thin pressure-sensitive film, characterized in that: The MOF-based ultra-thin pressure-sensitive film is a sandwich structure, wherein the top layer and the bottom layer are encapsulation layers, and the middle layer is a MOF layer; The encapsulation layer is made of encapsulation material, and the thickness of the encapsulation layer is 1-2 μm; The MOF layer is synthesized by ultrasonic crushing method to form a nano-sized MOF material with piezochromic properties, and the MOF layer is prepared by scraping method, and the thickness of the MOF layer is 4-5 μm; The MOF-based ultra-thin pressure-sensitive film can realize visual pressure detection.

2. The method for preparing the MOF-based ultra-thin pressure-sensitive film according to claim 1, characterized in that: The packaging material includes any one of the following: Epoxy resins, polyimides, polyurethanes, polyvinyl alcohol, polyethylene terephthalate, polydimethylsiloxane, polycarbonate and paraxylene polymers.

3. The method for preparing the MOF-based ultra-thin pressure-sensitive film according to claim 1, characterized in that: The nano-sized MOF synthesis method is an ultrasonic crushing method, the dosage ratio of MOF material to N, N-dimethylformamide is 28-32 mg: 3-5 mL, the power of ultrasonic crushing is 19.5-20.5 KHz, and the ultrasonic time is 1-2 hours.

4. The method for preparing the MOF-based ultra-thin pressure-sensitive film according to claim 1, characterized in that: The piezochromic MOF material includes at least one of the following materials: LIFM-66, PCN-128, NKU-200-Eu, HNU-49, DEF® ZnETTB and LIFM-102.

5. The method for preparing the MOF-based ultra-thin pressure-sensitive film according to claim 1, characterized in that: During the preparation of the MOF layer, MOF is dispersed in a polymer solution, and the polymer includes any one of the following: Polyethylene, polypropylene, polyvinyl chloride, polystyrene, polycarbonate, polymethyl methacrylate, polyamide, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyvinyl pyrrolidone, polydimethylsiloxane, polylactic acid, polycaprolactone, polybutylene succinate.

6. The method for preparing the MOF-based ultra-thin pressure-sensitive film according to claim 1, characterized in that: The MOF layer preparation process is a scraping method, and the specific steps are as follows: Step A1: dispersing the nano-sized piezochromic MOF material in a polymer solution to prepare a scraping dispersion solution, and taking 50-60 μL of the scraping dispersion solution; Step A2: Set the scraper height to 10-30 μm and the speed to 55-62 mm·min -1 ; Step A3: Place the scraped MOF layer on a 95-105°C heating plate for 1-3 min.

7. The method for preparing the MOF-based ultra-thin pressure-sensitive film according to claim 1, characterized in that: The calculation method for quantifying the pressure distribution in the compressed area is as follows: first, images of the pressure-sensitive film before and after compression are collected, and characteristic values ​​of the images before and after compression are extracted using an image processing algorithm; then, the color difference ΔE is calculated, and a linear relationship between ΔE and the pressure magnitude is established; finally, visual detection of the pressure distribution is achieved by performing color difference calculation on the collected images.

8. The method for preparing the MOF-based ultra-thin pressure-sensitive film according to claim 1, characterized in that: The MOF-based ultra-thin pressure-sensitive film is used in the fields of piezochromic film preparation and interface stress detection.

Citation Information

Patent Citations

  • A method for preparing small-sized amorphous MOF hybrid matrix membranes with high selectivity

    CN113198331B

Cited By

  • MOF thermal insulation layer enhanced photo-thermal composite desalination membrane and preparation method thereof

    CN120885060A